Promoting independent living and recreation in life through ambient assisted living technology - Costa, Ângelo (2015)
The increase in life expectancy with a decrease in birth rates is contributing to the ageing of the European population. This phenomenon, coupled with greater awareness of the quality of life, the need to have cost-efficient assistive care, the intention of people to live independently in their homes, and the technological developments in recent decades, have contributed to the emergence of the concept of ambient assisted living (AAL). AAL solutions aim to provide healthy and safe ageing to users through promoting independence in performing daily activities and interacting with technology, taking into consideration the deterioration of the users’ capabilities and the reduced costs of the solutions. In this chapter, AAL developments of monitoring activities of daily living (ADLs) and participation in a virtual community with the selected stakeholders are introduced, their roadmap with the expected technological developments are described, and the expected impact of these solutions on the end users of the developed solutions are discussed. This enables a real user guidance structure that represents the different needs and limitations of each user, presenting a highly structured project based on personas and possible solutions for them. The AAL4ALL Ambient Assisted Living for All (ALL4ALL) project is considered here as a case study to analyze and illustrate the ALL concepts discussed in this chapter.